2012
DOI: 10.1017/s0305000912000232
|View full text |Cite
|
Sign up to set email alerts
|

Lexical composition in children with autism spectrum disorder (ASD)

Abstract: For sixty-seven children with ASD (age 1;6 to 5;11), mean Total Vocabulary score on the Language Development Survey (LDS) was 65·3 words; twenty-two children had no reported words; and twenty-one children had 1–49 words. When matched for vocabulary size, children with ASD and children in the LDS normative sample did not differ in semantic category or word-class scores. Q correlations were large when percentage use scores for the ASD sample were compared with those for samples of typically developing children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…Only one prior study has investigated lexical differences at the word level (Rescorla and Safyer 2013) and concluded, based on the large degree of overlap among the most frequently used words, that lexical composition was delayed but not atypical in children with ASD. Our study does not dispute the large degree of similarity in lexicons or lexical development, but aims to focus the discussion on the degree of lexical differences present in infants with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one prior study has investigated lexical differences at the word level (Rescorla and Safyer 2013) and concluded, based on the large degree of overlap among the most frequently used words, that lexical composition was delayed but not atypical in children with ASD. Our study does not dispute the large degree of similarity in lexicons or lexical development, but aims to focus the discussion on the degree of lexical differences present in infants with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has investigated lexical composition at the word level in children with ASD (Rescorla and Safyer 2013) using the Language Development Survey (LDS; Rescorla 1989), a parent report measure of expressive language. The authors concluded that the children with ASD were acquiring essentially the same words as children with typical development.…”
Section: Studies Conducted After Asd Diagnosismentioning
confidence: 99%
“…A few studies have examined the composition of the lexicon more broadly to ask whether children with ASD know the same kinds of words as TD children. Rescorla and Safyer [] found that though children with ASD had smaller vocabularies than TD children, there were no significant differences in the kinds of words they knew whether by grammatical category (e.g., noun, verb), or semantic category (e.g., animal names, toy names). Similar results have been reported using the MacArthur‐Bates Communicative Development Inventory [Charman et al, ; Luyster et al, ], and in comparison to late‐talking toddlers [Weismer et al, ], although nonsemantic properties like word length do appear to matter [Kover & Ellis Weismer, ].…”
Section: Access To a Lexicon: Using Language Inputmentioning
confidence: 99%
“…Much of the research we have reviewed on the underlying structure and use of lexical categories in ASD suggests that it is relatively intact [e.g., Charman et al, ; Luyster et al, ; Rescorla and Safyer, ]. One caveat is that lexical entries that are highly embedded in complex social cognitive skills (such as perspective‐taking and Theory of Mind) may be impaired, including deictic terms [Hobson, Garcia‐Perez, & Lee, ] and mental state and emotion words [e.g., Hobson & Lee, ; Tager‐Flusberg, ].…”
Section: Access To a Lexicon: Using Language Inputmentioning
confidence: 99%
“…Expressive language is often the first reported parental concern for children later diagnosed with ASD (De Giacomo & Fombonne, 1998;Herlihy, Knoch, Vibert, & Fein, 2015), and thus previous work has comprehensively explored the possible link between language and ASD (see Boucher, 2012 for a review). This previous work highlights that a range of language ability exists in the ASD population, in that there is a subset of children who present with intact structural language abilities (Grzadzinski, Huerta, & Lord, 2013); however, there is also a substantial number of individuals with ASD who also present with concomitant language difficulties (Buschmann et al, 2008;Luyster, Qiu, Lopez, & Lord, 2007;Rescorla, 2011;Rescorla & Safyer, 2013).…”
Section: Introductionmentioning
confidence: 97%